How to do a laparoscopic high left colectomy with complete mesocolic excision and central vascular ligation for splenic flexure cancer. Issue 5 (5th April 2019) - Grama, Florin; Chitul, Andrei; Bezede, Cosmin; Burcoş, Traean; Cristian, Daniel
Abstract : Due to a lack of a standardized surgical approach in splenic flexure cancer, we consider useful to present a how to do it material on laparoscopic high left colectomy with complete mesocolic excision and central vascular ligation for this type of tumours.